DEVELOPMENT OF MALAYSIA UNDER THE LEADERSHIP OF MAHATHIR MOHAMAD: TURNED MALAYSIA INTO A RICH COUNTRY - Reza, Manjurul Hossain; Yasmin, Nilufar (PEOPLE: International Journal of Social Sciences, 2019)
If any person wants to know and learn about leadership, he or she must have to learn from Mahathir Mohamad about leadership, how to lead the people, and how to turned into the rich country from a poor agricultural economy. He is known as the Father of Modernization for Malaysia. In this respect, dynamic reforms which have taken place in the context of whole Malaysia owe much to the leadership of Mahathir Mohamad. His leadership ability led the community to grow from lower level to upper level and the achievement unparalleled neither by any contemporary leader nor at the present time. He is a true patriot and a multi-talented leader where he was able to achieve a breakthrough in a short period of time. The purpose of this writing is to know about the leadership qualities of Mahathir Mohamad, achievements, and effective ruling ideas which turned Malaysia into a rich and developed country. This paper has written based on the analysis of literature review of some previous works about Mahathir Mohamad and Malaysia.